1997
DOI: 10.1038/ki.1997.310
|View full text |Cite
|
Sign up to set email alerts
|

In situ hybridization studies of matrix metalloproteinase-3, tissue inhibitor of metalloproteinase-1 and type IV collagen in diabetic nephropathy

Abstract: Progressive expansion of the mesangial matrix is one of the most characteristic histological features of diabetic nephropathy (DN). To determine the balance between the turnover and degradation of extracellular matrix (ECM) in renal tissue of patients with DN, we examined the expression of matrix metalloproteinase-3 (MMP-3), tissue inhibitor of metalloproteinase-1 (TIMP-1) and type IV collagen (IV-C) mRNAs using a high-resolution in situ hybridization. Patients were divided into three grades: mild (grade I), m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
75
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 38 publications
9
75
0
2
Order By: Relevance
“…Matrix metalloproteinase inhibitor gene 1 (Timp-1) was also found to be up-regulated in the kidney tissue of the T2D rats, consistent with a report by Suzuki et al (18), which showed that the expression of the Timp-1 gene was up-regulated in renal parenchymal and infiltrating cells in patients with ND. TIMP-1 is thought to play a role in resistance to lymphocyte-mediated apoptosis in vivo by decreasing the activity of NF-κB (19).…”
Section: Discussionsupporting
confidence: 78%
“…Matrix metalloproteinase inhibitor gene 1 (Timp-1) was also found to be up-regulated in the kidney tissue of the T2D rats, consistent with a report by Suzuki et al (18), which showed that the expression of the Timp-1 gene was up-regulated in renal parenchymal and infiltrating cells in patients with ND. TIMP-1 is thought to play a role in resistance to lymphocyte-mediated apoptosis in vivo by decreasing the activity of NF-κB (19).…”
Section: Discussionsupporting
confidence: 78%
“…Although induction of MMP-3 and MMP-9 are well documented in glomerular disease, 31,32 expression of MMP-12 in normal or diseased glomeruli has not been documented, with the exception of autoimmune glomerulonephritis, where the MMP-12 expression is due to infiltrating macrophages. 18 Kidneys from wild-type and 7-week-old Alport mice were immunostained using antibodies specific for MMP-12.…”
Section: Mmp-12 Expression Is Markedly Induced In Glomeruli From Alpomentioning
confidence: 99%
“…In particular, the mechanism underlying the expansion of the mesangial matrix remains poorly defined. Although some observations have suggested increased ECM synthesis to be the major cause, this was not universally found (Fukui et al, 1992;Suzuki et al, 1997). It has been suggested that there are qualitative changes in the ECM leading to alterations in the glomerular basement membrane (GBM) proteoglycan content, thus affecting the GBM charge (Wayl et al, 1982).…”
mentioning
confidence: 99%